Decomposition mechanism of polyesters based on 2, 5-furandicarboxylic acid and aliphatic diols with medium and long chain methylene groups. (October 2016) - Terzopoulou, Zoe; Tsanaktsis, Vasilios; Nerantzaki, Maria; Papageorgiou, George Z.; Bikiaris, Dimitrios N.
Abstract: Three different polyesters have been synthesized using 2, 5-dimethylfuran dicarboxylate (DMFD) and diols with 5, 6 and 9 methylene groups, namely poly(pentylene 2, 5-furanoate) (PPeF), poly(hexylene 2, 5-furanoate) (PHF) and poly(nonylene 2, 5-furanoate) (PNF), respectively. These polyesters that can be prepared from monomers derived from renewable resources were synthesized by melt polycondensation technique. Their structure was confirmed by 1 H NMR spectroscopy. Thermal stability of polyesters was investigated using thermogravimetric analysis (TGA) and their decomposition mechanism was evaluated with Pyrolysis-Gas chromatography/Mass spectroscopy (Py–GC/MS). It was found that all polyesters decompose with a similar way and decomposition takes place mainly via β-hydrogen bond scission and less extensive with homolytic scission.